Post Eruption inflation of the East Pacific Rise at 9°50′ N - Scott L. Nooner; Spahr C. Webb; W. Roger Buck; Marie‐Helene Cormier (Geochemistry, Geophysics, Geosystems, 2014)
Abstract In June 2008, we installed a geodetic network at 9°50′ N on the East Pacific Rise to track the long‐term movement of magma following the 2005/6 eruption. This network consists of 10 concrete benchmarks stretching from the ridge to 9 km off‐axis. During three campaign‐style surveys, measurements of vertical seafloor motions were made at each of these benchmarks by precisely recording ambient seawater pressure as a proxy for seafloor depth with a mobile pressure recorder (MPR). The MPR was deployed using the manned submersible Alvin in 2008 and 2009 and the remotely operated vehicle Jason in 2011. The MPR observations are supplemented with data from a multiyear deployment of continuously recording bottom pressure recorders (BPRs) extending along this segment of the ridge that can record rapid changes in seafloor depth from seafloor eruptions and/or dike intrusions. These measurements show no diking events and up to 12 cm of volcanic inflation that occurred from December 2009 to October 2011 in the area of the 2005/6 eruption. These observations are fit with an inflating point source at a depth of 2.7 km and volume change of 2.3 × 106 m3/yr located on the ridge axis at approximately 9°51.166′ N, 407 m from our northernmost benchmark, suggesting that the magma chamber underlying this segment of the ridge is being recharged from a deeper source at a rate that is about half the long‐term inflation rate observed at Axial Seamount on the Juan de Fuca Ridge. These data represent the second location that active volcanic uplift has been measured on a mid‐ocean ridge segment, and the first on a nonhotspot influenced segment.